Kegiatan Manajemen Peserta Didik di Sekolah - Wardah Sahrani Sibarani; Lola Amalia Sibarani; Yusuf Ali Ahmad Harahap; Amaluddin Tanjung; Rizki Akmalia (Departement of Mathematics Education, 2023)
Student management is very much needed in educational institutions because students are both subjects and objects in the process of transforming knowledge and skills. Success in the implementation of education will depend heavily on the development of the physical, intellectual, social, emotional and psychological potential of students. Acceptance of students is a process of finding, determining, and attracting potential applicants who are able to become students in the educational institution (school) concerned. Furthermore, Mustari explained that student acceptance is a process of data collection and service to students who have just entered school, after they meet the requirements set by the school ahead of the new school year.